TEKNOLOGI PROSES PRODUKSI SENSOR CAHAYA UNTUK PENGEMBANGAN ROBOTIK BERBASIS TEKNOLOGI LAPISAN TIPIS BAHAN FERROELEKTRIK BARIUM STRONSIUM TITANAT (BA0,55SR0,45TIO3) - Faanzir Faanzir; Umar Umar (Jurnal Media Elektro, 2013)
Ferroelectric thin films have been used for different applications in the fields of electronics and electric-optics. Barium Strontium Titanate (BST) is very attractive ferroelectric material and becomes the center of attention due to its various advantages, including low optical losses, low dielectric constant and high storage capacity. The purpose of this research is to find the optical and crystal structure properties of thin-film Ba0,55 Sr0.45Tio3 (BST)1 M. Annealing time was 15 hours at a temperature of 750°C and 775oC on p-type silicon subtract by using chemical solution decomposition (CSD) methods which is followed by spin coating process at 3000 rpm for 30 seconds. Optical properties test such as absorbance and transmittance analysis, showed that the increase in the annealing temperature can improve the absorbance properties and energy gap of BST. Energy gap obtained by using tauc plot are 3.05 eV for the annealing temperature of 750°C and 3.225 eV for the annealing temperature of 775oC. Crystal structure by X-Ray Diffraction (XRD) showed that the difference in annealing temperature causes a shift in the angle of diffraction. The pseudo tetragonal structure of Ba0,55 Sr0.45Tio3 becomes tetragonal (c / a <1) and the crystal structure have crystal orientation distribution.